MRI image distortion due to magnetic materials in medical implants - Harberts, Dick W.; van Helvoort, Mark (2015 IEEE International Symposium on Electromagnetic Compatibility (EMC), 2015)
Currently, research activities are underway to create coexistence between active implantable medical devices and Magnetic Resonance Imaging (MRI). One of the questions is if ferrite materials can be used for miniature transformers for EMI suppression. Commonly it is known that the use of magnetic materials should be minimized in and near an MRI scanner because MRI employs large magnetic fields with which any magnetic material will be subject to strong forces. In addition, magnetic materials may introduce image artifacts and reduce diagnostic image quality. The analysis presented in this paper shows that the requirements on diagnostic image quality pose higher limitations on the use of magnetic materials in medical implants than the requirements for magneto-mechanical forces. From experiments with ferrites in a 1.5-T MRI system, it is concluded that if diagnostic image quality is required for distances of at least 2 cm from the medical implant, then only 0.1 mm 3 ferrite can be accepted. This amount of ferrite is too low for any practical application. Therefore, medical implants can only be coexistent with MRI if they do not contain ferrites.